Influencia del flujo del líquido de diálisis en los parámetros de calidad de la hemodiafiltración en línea post-dilucional. - Crehuet-Rodríguez, Isabel; Ramírez-Crehuet, Marta; Méndez-Briso-Montiano, Pilar; Mulero-San José, Maria Teresa (Enfermería Nefrológica)
Introduction: Online post-dilution hemodiafiltration is a variant of hemodialysis that, according to different studies, can increase patient survival. Initially, and unlike conventional hemodialysis, very high dialysate flows were used (up to 700-800 ml/min), new studies questioned the usefulness of elevation to achieve purifying efficacy. Objective: To analyze the differences produced in Kt, Kt/V and infusion volume in post-dilutional online hemodiafiltration using a dialysate flow at 600 ml/min and 500 ml/min, as well as to evaluate the impact on the consumption of water during the session. Method: 22 dialyzed chronic patients undergoing postdilutional hemodiafiltration on Artis® monitors were included. 440 sessions were studied, 220 with each flow. Age, time of permanence in technique, Kt, Kt/V and infusion volume were studied. Results: Of the 22 patients, 7 were women, with a median age of 79.5 years (range 40-86) and a mean dialysis time of 25.13±10.51 months. The mean values for dialysate flows of 600 ml/min and 500 ml/min were respectively: Kt: 45.5±9.4 and 45.2±9.2 liters, Kt/V: 1.52±0.33 and 1.51±0.33, and infusion volume: 21.84±4.50 and 21.94±4.51 liters. Conclusions: According to our results, on-line post-dilution hemodiafiltration can be dialyzed with dialysate flows of 500 ml/min without impairing the hemodialysis quality parameters. The decrease in dialysate flow from 600 to 500 ml/min in post-dilutional on-line hemodiafiltration does not produce a loss in quality parameters and allows to reduce water consumption.